Using Smartphones as Learning Media to Improve Vocabulary: A Focus on Senior High School Students - Lim, Citra Dewi (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Students at public senior high school 1 Long Bagun consider vocabulary learning difficult. In fact, vocabulary is an important element in communication. The purpose of this study was to determine the effect of using smartphones as a learning medium on improving students' vocabulary. This type of research employs a descriptive qualitative approach, incorporating a phenomenological perspective. The subjects of this study were students of public senior high school 1 Long Bagun, East Kalimantan. We collected data through interviews and documentation. The data analysis technique employed qualitative methods such as data reduction, data presentation, and conclusion/verification drawing. The results of this study indicate that there is an increase in students' vocabulary mastery after using smartphones as a learning medium. The overall exercise results clearly demonstrate this. Up to 90% of students can enhance their practice, indicating that the use of smartphones aids in vocabulary enrichment. Furthermore, observations and interviews reveal that students find motivation in the teaching and learning process when using smartphones as a learning medium. In conclusion, the use of smartphones as a learning medium has a significant impact on improving students' vocabulary mastery.